THE POSITION OF THE TURKESTAN EDUCATIONAL SYSTEM IN THE LATE 19TH AND EARLY 20TH CENTURIES AND THE SIGNIFICANCE OF JADIDIST IDEAS IN ITS DEVELOPMENT - Baxritdin Samiyevich Turdiyev (Western European Studies, 2024)
This article discusses processes related to the emergence of ideas of modernism in Turkestan in the late 19th - early 20th century, reform movements in the education system, as well as the historical significance of the modern educational movement in the analysis of cultural and educational life of the country.
Keywords: Turkestan land; contemporaries; intelligentsia of Turkestan